Analisis Pendapatan Petani Karet di Nagari Tebing Tinggi Kecamatan Pulau Punjung Kabupaten Dharmasraya - Willion, Racel Joy Mikesi; Budiraharjo, Kustopo; Handayani, Migie (Universitas Galuh, 2024)
Rubber is one of the second largest plantation commodities after oil palm. Pulau Punjung is the sub-district with the largest rubber plantation area in Dharmasraya Regency, which is 6,980 ha. Nagari Tebing Tinggi is one of the Nagari which has a community with the main livelihood as a rubber farmer to make ends meet. The research objectives were to analyze rubber farming income and analyze the relationship between the variables of land area, total production, selling price, number of trees, and labor with the income of rubber farmers in Nagari Tebing Tinggi. The research was conducted in March-April 2023. The research method used was a survey. Data collection methods using observation and interviews. The sampling method used was simple random sampling, with a sample of 114. Data analysis using income analysis and Pearson correlation analysis. The results showed that the average production costs incurred were IDR 664,721.57/year, the average revenue was IDR 24,511,528.42/year, and the average income earned was IDR 23,846,806.86/year. Based on the results of the study, it is known that rubber farming in Nagari Tebing Tinggi makes a profit, with a profitability of 35.87%. The factors of land area, total production, and number of trees have a very significant relationship to income with a strong correlation level. The labor factor has a very significant relationship to income but the level of correlation with income is weak. The selling price factor is also significantly related with a very weak correlation level with income.